Hedging at Sea: Indonesia–Russia Defense Diplomacy through ORRUDA 2024 in the Indo-Pacific - Norlyanti, Nia; Perwita, Anak Agung Banyu; Hendarwoto, Yermia (Darul Yasin Al Sys, 2025)
Amid intensifying great-power rivalries in the Indo-Pacific, Indonesia’s defense strategy has shifted toward multidirectional engagement to preserve strategic autonomy without committing to any single bloc. This study examines the strategic significance of the ORRUDA 2024 joint naval exercise between Indonesia and Russia as a case of defense diplomacy within a hedging framework. Drawing on neorealism, hedging theory, and the actor–process–issue model of defense diplomacy, the research adopts a qualitative case study approach that integrates primary sources, including press releases and official statements, with secondary scholarly literature. The findings reveal that ORRUDA operates both as a balancing mechanism against U.S.-led regional security architectures such as AUKUS and the Quad, and as a diplomatic signal affirming Indonesia’s bebas-aktif foreign policy. The exercise strengthens operational cooperation with non-Western partners, reinforces national security, and contributes to regional stability. It also demonstrates the utility of defense diplomacy as a non-aligned, peacetime instrument of strategic statecraft involving coordinated planning, communication, and issue-specific collaboration. Overall, the analysis underscores the role of calibrated, non-provocative military engagement in managing geopolitical uncertainty and highlights the importance of diversifying defense partnerships and enhancing strategic communication to sustain Indonesia’s agency in a contested Indo-Pacific environment.